The effect of adding sodium tripolyphosphate on thiobarbituric acid value, crispiness, and organoleptic on salted egg crackers - Siti Susanti; Rafli Zulfa Kamil; Finky Firsya Fardiah (Institute of Advanced Engineering and Science, 2023)
Crackers are one of the dry foods that can experience volume expansion when fried. Salted egg crackers are a form of innovation and product diversification in crackers, which are made using ingredients containing starch and various other additives. This study aims to determine the exact concentration in the use of sodium tripolyphosphate as a crunch in dough on the crispness, thiobarbituric acid (TBA) value, and organoleptic of the salted egg crackers. There were 4 sodium tripolyphosphate (STPP) concentration treatments, namely 0% (T1), 0.25% (T2), 0.5% (T3), and 0.75% (T4). This research method consists of experimental design, research procedures, parameter tests, and data analysis. The results of the analysis of the TBA value showed that the difference in the concentration of STPP affected the rancidity of the salted egg crackers, where the higher the concentration of STPP, the higher the TBA value. Crispness and organoleptic analysis showed the highest value and overall preference, namely 0.75% (T3) treatment. This study concludes that the difference in the concentration of the addition of sodium tripolyphosphate affects the crispness of crackers.